2018
DOI: 10.1186/s12962-018-0125-8
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating MCDA into HTA: challenges and potential solutions, with a focus on lower income settings

Abstract: BackgroundMulticriteria decision analysis (MCDA) has the potential to bring more structure and transparency to health technology assessment (HTA). The objective of this paper is to highlight key methodological and practical challenges facing the use of MCDA for HTA, with a particular focus on lower and middle-income countries (LMICs), and to highlight potential solutions to these challenges.Methodological challengesKey lessons from existing applications of MCDA to HTA are summarized, including: that the socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The main areas in which MCDAs are applied are in the diagnosis and treatment of pathologies, prioritization policies, and the evaluation of health technologies [2]. MCDAs have been used by various public and private health technology assessment organizations and agencies in different countries [13], such as Germany [14], Norway [15], Italy [16], Australia [17], and Thailand [18,19].…”
Section: Disability (P=0021) 5%mentioning
confidence: 99%
“…The main areas in which MCDAs are applied are in the diagnosis and treatment of pathologies, prioritization policies, and the evaluation of health technologies [2]. MCDAs have been used by various public and private health technology assessment organizations and agencies in different countries [13], such as Germany [14], Norway [15], Italy [16], Australia [17], and Thailand [18,19].…”
Section: Disability (P=0021) 5%mentioning
confidence: 99%
“…The low rate of studies conducted could limit the number of reports published in the grey literature. Despite the small number of the included studies, this review was able to confirm the importance of addressing uncertainties surrounding the economic evaluation's estimates to inform decision making in LMICs, which was also indicated in other studies [21,37]. Most of the included studies also showed consistent costeffectiveness findings.…”
Section: Discussionmentioning
confidence: 56%
“…Drug value evaluations should consider multiple dimensions and criteria. [50, 51] The NHI formulary listing of drugs often takes into consideration the comparative efficacy, comparative safety, cost-effectiveness, and overall expenditures. However, the results showed that if only the four criteria above are considered, only 57.5% of the weights are covered.…”
Section: Discussionmentioning
confidence: 99%